Penggunaan Media Sosial dalam Meningkatkan Karakter Semangat Cinta Tanah Air (Studi Kasus Mahasiswa Universitas PGRI Sumatera Barat) - Nisa, Radiyatul; Juliardi, Budi; Namzi, Ranti (Asian Journal of Early Childhood and Elementary Education, 2023)
Technological progress is something that cannot be avoided, because technological progress is in line with scientific progress. One of them is internet technology which has a major influence on human life in daily activities. With the increasing number of social media users, it is assumed that the pattern of communication behavior also changes. As in the communication process, someone who uses the internet does not only act as a media user but can also be a creator such as social media influencers. The attitude of loving the motherland is an attitude that prioritizes the interests of the nation and an attitude of being willing to sacrifice for the glory of the nation and the country. Every citizen must have an attitude of love for the motherland. This love for the motherland is what makes a person care about his nation and country. In the era of digital society 5.0, the attitude of loving the motherland is important. This era is an era where developments occur not only in the technology sector but in all sectors of life. As Indonesian citizens who live in digital society 5.0, an attitude of love for the motherland must be manifested through various innovative and creative activities. This research is a study focused on students to maintain the spirit of love for their homeland. The purpose of this research is for students to be able to have a high spirit of nationalism in the era of digital society 5.0 which is expected to become the next generation who are smart, skilled and able to become citizens who are able to carry out their obligations with full sense of responsibility. This study uses a qualitative approach to the case study method. Therefore, the existence of social media can increase a high sense of patriotism for students in the era of digital society 5.0. In addition, from this research, there are several ways that can be done to increase the attitude of love for the motherland, such as studying hard, preserving and introducing Indonesian culture to the international world, using and buying domestic products and making Indonesia proud by participating in a number of international competitions.